2019
DOI: 10.1155/2019/7513404
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Effect of Plant Extract on Mesenchymal Stem Cell Proliferation and Differentiation

Abstract: Stem cell has immense potential in regenerative cellular therapy. Mesenchymal stem cells (MSCs) can become a potential attractive candidate for therapy due to its remarkable ability of self-renewal and differentiation into three lineages, i.e., ectoderm, mesoderm, and endoderm. Stem cell holds tremendous promises in the field of tissue regeneration and transplantation for disease treatments. Globally, medicinal plants are being used for the treatment and prevention of a variety of diseases. Phytochemicals like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 141 publications
0
42
0
Order By: Relevance
“…Literature data indicate that various compounds of plant origin have a different effect on cell proliferation, hence the content of individual compounds and interactions between them will strictly affect the final effect of the extracts 76 . Also, the concentration of individual compounds in the obtained extracts is of great importance for the effect of their action on cells, as numerous studies indicate a dose-dependent effect of compounds of plant origin 77 . The anthocyanins and anthocyanidins contained in the tested plants can also affect cell viability, because, as shown by studies by Wang et al, in low concentrations these compounds can cause arrest in the G0/G1 phase of the cell cycle, while at higher concentrations the cycle is inhibited in phase G2/M.…”
Section: Resultsmentioning
confidence: 99%
“…Literature data indicate that various compounds of plant origin have a different effect on cell proliferation, hence the content of individual compounds and interactions between them will strictly affect the final effect of the extracts 76 . Also, the concentration of individual compounds in the obtained extracts is of great importance for the effect of their action on cells, as numerous studies indicate a dose-dependent effect of compounds of plant origin 77 . The anthocyanins and anthocyanidins contained in the tested plants can also affect cell viability, because, as shown by studies by Wang et al, in low concentrations these compounds can cause arrest in the G0/G1 phase of the cell cycle, while at higher concentrations the cycle is inhibited in phase G2/M.…”
Section: Resultsmentioning
confidence: 99%
“…This gives confidence to the use of CGF in cell expansion designated for TERM applications. Given prior studies have shown that plant extracts are capable of stimulating differentiation in MSC, it is important to conduct future complementary investigations to understand the effect of CGF on the differentiation potential of 3D-cultuired ADSC (Zhang et al, 2015;Imran et al, 2017;Saud et al, 2019).…”
Section: Cgf Supplementation Preserved Mammalian Cell Function and Phmentioning
confidence: 99%
“…In this context, a new research stream has been evolving to use medicinal plant extracts as stimulants of stem cells because of their high availability, low toxicity, and minimum side effects (Udalamaththa et al, 2016;Kornicka et al, 2017;Udagama and Udalamaththa, 2018;Saud et al, 2019). However, despite the fact that hAECs were discovered decades ago, few researches have been done on using natural compounds to optimize the microenvironment or to regulate the early biological events for controlled differentiation of hAECs.…”
Section: Introductionmentioning
confidence: 99%